Fiber Is the New Painting. - Vogel, Wendy (Art in America)
The article reports that several artists are using fiber in ways that look a lot like painting. It informs that artist Natalia Nakazawa uses textiles to address cultural heritage, diaspora, digital circulation, and institutional power. It makes reference to the "The New Bend," a group show at Hauser & Wirth gallery, featuring connection between artists such as Tomashi Jackson, Eric N. Mack, and Basil Kincaid.